BEYOND WHATSAPP PROFILE PICTURE: PERSONALITY PRESENTATION, SELF-DISCLOSURE, AND IMPRESSION MANAGEMENT OF 2021 FRESHMEN IN MALANG - Hidayatullah, Muhammad Alfian; Bhakti, Aditya Dwi Putra; Nasvian, Moch Fuad (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2023)
Profile photos are an integral part of most online media platforms as it allows account owners to connect with a wider variety of online communities. Profile photos can also be used to describe self-disclosure in online communications, hence, the users are often confused about choosing an image or photo to describe themselves. For freshmen of the Covid-19 generation, profile photos on social media are part of impression management because they are required to have full interactions through online platforms, especially WhatsApp, without prior direct interaction. In this situation, usually, most freshmen will use their best photos as profile photos with the aim of inviting interaction with other freshmen so they can start exchanging messages on WhatsApp. This research aims to depict how WhatsApp profile pictures reflect the personalities, emotions, and self-disclosure of freshmen in the class of 2021 (Covid-19 Generation) in Malang, Indonesia, and what is the role of Impression Management in CMC communication, WhatsApp in this case. The research was carried out using thematic analysis, using the IPIP-NEO 30 instrument. The results of the study show that there is a fairly strong relationship between WhatsApp profile pictures and the personalities of freshmen in the class of 2021 (Covid-19 Generation) in Malang. Also, the WhatsApp profile pictures speak a lot about their emotion and mental state as they attempt to communicate through images. Furthermore, the WhatsApp users in this case consciously choose images representing themselves. It means that they are aware of their self-disclosure and Impression Management in CMC communication, in this case, WhatsApp.